Improvement of Helicobacter pylori eradication efficacy at stomach and duodenum peptic ulcers - Natalya O. Schanova; Lyudmila V. Prokhorova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate efficacy of the modified sequential therapy regimen of Helicobacter pylori (H. pylori) eradication (with addition of bismuth tripotassium dicitrate) at treatment of peptic ulcer of the stomach (PUS) and duodenum (PUD) of severe and complicated course in the Russian population. Material and methods. Original study included overall 105 patients with PUS and PUD with severe and complicated course of disease. The main group received modified sequential therapy regimen, the comparison group - standard triple mode. All patients underwent quantitative serological test for H. pylori-specific IgG antibodies, stool test for H. pylori antigen, fibrogastroscopy with stomach mucosa (SM) biopsy and rapid urease test, microscopic examination of SM biopsy specimens, polymerase chain reaction for H. pylori DNA in SM biopsy specimens. Results. Efficacy of H. pylori eradication at modified sequential therapy was 95,8%, at standard, also combined with bismuthate tripotassium dicitrate, - 86,4%. After successful H. pylori eradication decrease of inflammatory activity of the stomach mucosa at less prominent decrease of mononuclear infiltration was noted, however the tendency for reduction of these features was more significant in patients at modified sequential regimen. Conclusions. Growth of H. pylori antibiotic resistance requires accumulation of the Russian data on efficacy of sequential therapy to increase eradication rate and prevent growth of macrolide resistance. Sequential therapy was proposed as a way to overcome resistance to clarithromycin. Sequential eradication therapy with inclusion of bismuth tripotassium dicitrate has shown advantage over standard triple therapy at severe and complicated forms of gastroduodenal peptic ulcers. Results of original study allow to recommend sequential eradication therapy in Russia. Key words: peptic ulcer, Helicobacter pylori, eradication, modified sequential therapy, bismuth tripotassium dicitrate.